Carbon Emission and Optimization of Energy for Sustainable Development: Rethinking the Possibility - Idowu, Samuel Sunday; Mustapa, Siti Indati; Joshua, Segun (Frontiers in Energy Research, 2021)
The adverse effects of climatic change and environmental degradation associated with the fossil energy sources from crude oil, coal and gas have been used as a sad commentary by some transnational organizations and multilateral concern. Thus, such campaigns, actions, and concerted efforts are geared towards making them redundant while canvassing for renewable energy sources as perfect alternatives. Although gas is characterized by lower carbon emission, it is somehow not considered as a source capable of being improved upon for a sustainable energy source. Hence this research is undertaken to project the viability of gas energy with a minimum deleterious impact on nature and humanity. With secondary data sources, the study employed a descriptive research method and employed dynamic capabilities theory as a framework. It was discovered through the study that state politicking surrounds the current move to jettison the fossil energy, the multilateral concern also backsthe ploy towards its abandonment, resulting in the development of cold feet towards renewing interests in engaging science, technology and innovation to further decarbonizes the gas energy. The authors suggest, amongst others, the need for a deliberate engagement of a cutting edge research and innovative technology through collaborations among countries, international organizations such as OPEC and oil firms. If this is done, it will enhance its relevance even without compromising the minimum bio-safety and environmental standards.